Ireland and her neighbours in the seventh century - Richter, Michael (Four Courts Pr., 1999)
Irish society was the first outside the Roman Empire to receive Christianity, and to do so in Latin, which was soon to become customary elsewhere in the West. Since Ireland was spared the upheavals which characterized the post-Roman centuries in Western Europe, Latin learning unfolded there within a context of a vibrant native Irish culture. Why did Christians come to Ireland from abroad? Why, by contrast, did Irish Christians leave their native country to live abroad? These are some of the central questions posed in this book. It emerges that Ireland and Spain were the societies with the most dynamic Latin culture in the seventh century. Thus, Ireland emerges as the decisive mediator between late antiquity and the Western Middle Ages.
Keywords: Ireland